Gencat Seni ( Gerakan Cegah Stunting Sejak Dini ) untuk Mencegah Kejadian Stunting - Dian Eka Nursyam; Sandra Ilona; Erin Desweni (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
This community service activity aimed to improve the knowledge, attitudes, and behaviors of adolescent girls in preventing stunting from an early age through health education and the distribution of iron supplementation tablets as an effort to prevent anemia. The program was implemented through four stages: socialization of the activity to school authorities and participants, administration of pre-test and post-test questionnaires to measure knowledge, attitudes, and behaviors, health education on stunting and anemia, and the distribution of iron tablets with teachers involved as program evaluators. The results showed that 87% of participants had good knowledge, 11% had moderate knowledge, and 2% had poor knowledge. Positive attitudes toward stunting prevention were demonstrated by 68% of participants, while 32% remained neutral or less supportive. In terms of behavior, 45% of participants were in the moderate category, 40% in the good category, and 15% in the poor category. Overall, this community service program was effective in improving the knowledge and attitudes of adolescent girls; however, continuous education and mentoring are still needed to ensure consistent adoption of stunting prevention behaviors in daily life.